1975
DOI: 10.1111/j.1467-9310.1975.tb01240.x
|View full text |Cite
|
Sign up to set email alerts
|

A planning model of pharmaceutical research and development

Abstract: Despite the popular view that pharmaceutical research is a random process, and by inference unplannable, the long‐term survival and development of a pharmaceutical company must be based on a steady flow of new products with a full understanding by management of the relationships between research expenditure and the likely revenues they will produce. In this paper is developed a model of the R&D function which uses probabilistic assumptions to compute the expected stream of revenues from a portfolio of projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this short note, I have purposely limited discussion to the inclusion of a priori information in two common Poisson regression models, but it should be recognized that the method of offsets has much wider use, both within Poisson regression and, potentially, within linear modeling more generally. For example, Whitehead (1980;compare with Aitkin and Clayton 1980) has shown that the proportional hazards model of Cox (1972Cox ( , 1975 can be treated within the framework of Poisson regression using the method of offsets.…”
Section: Discussionmentioning
confidence: 99%
“…In this short note, I have purposely limited discussion to the inclusion of a priori information in two common Poisson regression models, but it should be recognized that the method of offsets has much wider use, both within Poisson regression and, potentially, within linear modeling more generally. For example, Whitehead (1980;compare with Aitkin and Clayton 1980) has shown that the proportional hazards model of Cox (1972Cox ( , 1975 can be treated within the framework of Poisson regression using the method of offsets.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis involved ANOVA testing 31 followed by post-hoc Tukey testing and calculation of covariance and Pearson and Spearman correlation coefficients; this analysis was performed in Python using the numpy, scipy, and statsmodels packages with the matplotlib package for plotting.…”
Section: Experimental Methodsmentioning
confidence: 99%